PENERAPAN METODE GREEDY DALAM OPTIMASI PENUKARAN UANG SEBESAR 125 RIBU RUPIAH - Piliang, Faisal (JREC (Journal of Electrical and Electronics), 2013)
Greedy method is the most popular method for solving the optimization problem; it is often also used to obtain the optimal solution of a problem. Issues optimization (optimization problems) is a matter of looking for the optimum solution. There are two kinds of optimization problems, namely maximization (maximization) and Minimize (minimization). The problem can be solved in such Greedy method is an optimization problem in exchange of money. In this journal, taken a case on the issue of how to optimize the exchange of money amounting to 125 thousand dollars? Keywords: Algorithms, Greedy method, Currency, Optimization.